PERANCANGAN SISTEM PEMBELAJARAN MATEMATIKA PADA ANAK SEKOLAH BERBASIS GAMIFIKASI MOBILE DENGAN METODE ADBO - Primaulidina, Fvediniar Edra; Siti Annisa Safitri; Latiful Muyassar; Anindo Saka Fitri (CV. Denasya Smart Publisher, 2025)
The COVID-19 pandemic has had a major impact on education, forcing learning to switch to an online system to prevent the spread of the virus. However, problems still persist, especially in elementary school mathematics education, students tend to think mathematics is difficult and not very interesting. This is due to the ineffective classroom learning approach, so that many students lose interest in learning mathematics. Therefore, innovative solutions are needed that can increase students' interest and understanding of mathematics learning, such as a gamification approach for students who prefer to play. The purpose of this study is to develop a mobile application that combines a gamification approach as a mathematics learning material for elementary school students. The system concept in this mobile application is that students can work on practice questions and see learning outcomes, choose an avatar on the edit profile, and access the discussion forum available in the application. This application is designed to create an interactive, fun and effective learning experience using the ADBO (Analyze, Design, Build, Operate) method which is systematic and directed to ensure that each stage of the process provides optimal results and according to user needs with the hope of overcoming complex problems faced by students. Through the modeling used in the preparation of this application, it is hoped that it will be in accordance with its purpose, namely to provide convenience to elementary school students, from grade 1 to grade 6, to become better at learning.